Effects of dietary fiber on growth, feed efficiency and nutrient utilization of tinfoil barb (Barbonymus schwanenfeldii, Bleeker 1853) fry - Mohamed Nafees, Mohamed Salihu; Kamarudin, Mohd Salleh; Karim, Murni; Hassan, Mohd Zafri; de Cruz, Clement Roy (Elsevier, 2023)
An 8-week feeding trial was conducted to determine dietary fiber utilization level in Barbonymus schwanenfeldii fry based on the growth, feed efficiency and nutrient utilization. Intestinal ±-amylase activity and liver and intestinal histology were used to evaluate the growth performance of fish. Five isonitrogenous (48 crude protein) and isocaloric (20.1 kJ g»1 gross energy) diets were prepared with different fiber levels (0.9, 3.18, 5.97, 8.34 and 10.73). Each diet was randomly assigned to triplicate groups of fish (0.557 ± 0.001 g) at 20 fry per 100 L glass aquarium. Results revealed that tinfoil barb fry tolerated 10.73 dietary fiber without compromising their growth. Average daily feed intake and feed conversion ratio linearly decreased with increasing fiber levels (P = 0.02). Protein efficiency had a positive association with dietary fiber levels (P = 0.03). Although whole body protein, ash and fiber contents were not related to dietary fiber levels, energy and lipid content linearly decreased with increased dietary fiber levels (P = 0.03). Retention of dietary protein and carbohydrate positively related to dietary fiber levels (P = 0.03). However, lipid and energy retentions were independent of dietary fiber concentrations. Intestinal ±-amylase activity showed a unique association with dietary fiber intake in intestinal bulb (P < 0.0001) and hindgut (P = 0.01). However, irrespective of higher midgut amylase activity, its specific content was independent of dietary fiber levels. Besides, there were not any histopathological signs on the gut and liver of fish fed 0.9“10.73 dietary fiber. Meanwhile, condition factor and viscerosomatic index were independent of dietary fiber. Since feeding 10.73 dietary fiber did not affect the growth performance and nutrient utilization, it was concluded that B. schwanenfeldii fry could tolerate 10.73 crude fiber in their practical diet. However, future studies are warranted to determine maximum tolerability of fiber by the fish using further increase in dietary fiber level.